Energetic Compact Strokes as the Major Source of Downward Terrestrial Gamma‐Ray Flashes in Winter Thunderstorms - Ting Wu; David M. Smith; Yuuki Wada; Kazuhiro Nakazawa; Manari Oguchi; Masashi Kamogawa; Tomoyuki Suzuki; Qingliu Yang; Daohong Wang (Geophysical Research Letters)
Abstract Terrestrial gamma‐ray flashes (TGFs) are short bursts of intense gamma radiation associated with lightning discharges. Although thousands of TGFs have been observed from space, TGFs detected at ground level, known as downward TGFs, are still very limited, and their relationship with lightning discharge processes remains elusive. Here we report a special type of strong negative lightning stroke, termed energetic compact stroke (ECS), in winter thunderstorms in Japan, and provide strong evidence that ECSs are consistently associated with downward TGFs. Based on this relationship, we successfully identified three new downward TGFs by the observations of ECSs. Further, 12 out of 19 (63%) of downward TGFs analyzed in this paper were associated with ECSs, indicating that ECSs are the major source of downward TGFs in winter thunderstorms in Japan. These findings open up the possibility of remotely monitoring a large fraction of downward TGFs with simple lightning observations.